The development of an early suburban industrial district: The Montreal ward of Saint-Ann, 1851–71 - Lewis, Robert (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1991)
The conventional description and explanation of industrial location in the nineteenth century emphasizes the concentration of production in the city core. In contrast this paper finds that for mid-nineteenth century Montreal a significant number of firms were locating on the urban fringe. In a case study of Saint-Ann ward between 1851 and 1871, it is shown that the Lachine canal was a powerful magnet attracting large-scale, technologically-advance industries. Other factors accounting for the development of this peripheral industrial district were cyclical change, new technologies, large capital investments, inter-industry linkages, and changes in the organizational structure of firms.